Environmental coastal monitoring of carbonate chemistry parameters in 2015-2017, South-West Baltic Sea - Sanders, Trystan; Thomsen, Jörn; Müller, Jens Daniel; Rehder, Gregor; Melzner, Frank (In: Sanders, T et al. (2020): Mussel calcification in the Baltic Sea under natural and manipulated carbonate chemistry parameters [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.925017, 2020)
This data set presents data from environmental coastal monitoring of carbonate chemistry parameters at the same 3 sites in the Baltic Sea over the course of 2 years. Poisoned water samples were analysed in laboratories in GEOMAR, Kiel and IOW, Rostock to understand the variation in carbonate chemistry and salinity and how this correlates with calcification rates of mussels in the field. These carbonate chemistry parameters were used to calculate aragonite saturation state (omega) and the ratio of calcification substrate to inhibitor (ESIR) to describe the environmental conditions relevant for calcification along the Baltic Sea salinity gradient.
Keywords: bicarbonate; calcification; calcium; Climate change; ESIR; Omega; Salinity; SIR